Iowa Birdline update, October 19, 1990, notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for October 19, 1990. Highlights of the notes include updates on previously seen birds, including a Sharp-tailed Sandpiper, a Mew Gull, a Scissor-tailed Flycatcher, and a California Gull. Epson - sheet feed/flatbed